Physical properties of french fries made with quinoa and opuntia-peel flours - Guerra, Roenfi; Leon, Alicia; Manzaneda, Eduardo; Apaza, Eva; Sucasaca, Angel; Medina, Wenceslao (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
A large part of the world population consumes fast food on a regular basis. Most of these menus are accompanied by french fries. Their consumption does not represent a major nutritional contribution, and the frying process incorporates a considerable amount of oil into the french fries, increasing the risks of diseases such as obesity. The objective of the present work was to evaluate the physical and textural properties of a potato chip substitute made by extrusion technology with the incorporation of flours of a nutritious cereal such as quinoa and prickly pear peel in its formulation. Color and porosity were evaluated by image analysis. Texture by mechanical compression tests with an Instron universal testing machine and oil absorption rate by a modified compression method. Sticks of a potato substitute were obtained and fried by immersion in oil at 180 °C in the same way as a commercial pre-fried product. The firmness of the sticks (4.5 N) is 30 % higher than the commercial product, while the oil absorption rate (6.25 %) of the products obtained is three times lower. This phenomenon could be due to the fiber content present in the prickly pear peel flour and protein content in the quinoa flour. It is concluded that is possible to elaborate products similar to traditional and commercial potato chips, so that, without altering the consumption habits of the population, it can allow the intake of healthier foods.